The Prevalence of PTSD in a Forensic Psychiatric Setting: The Impact of Traumatic Lifetime Experiences - Bianchini, Valeria; Paoletti, Giovanna; Ortenzi, Roberta; Lagrotteria, Brunella; Roncone, Rita; Cofini, Vincenza; Nicolò, Giuseppe (Frontiers in Psychiatry, 2022)
Background. Several studies have identified traumatic history among forensic patients and its association with criminal behaviors and psychiatric diagnoses. Post-traumatic stress disorder (PTSD) is highly prevalent in forensic settings causing a serious deterioration of the primary psychiatric disorder. Aims. Our study aims to evaluate the prevalence of PTSD and the role of traumatic experiences and abuse in the development of psychiatric disorder in a sample of psychiatric offenders with a history of violent behavior. Methods. Fifty-three patients admitted in Italian high intensity therapeutic facilities – the Residenze per l’Esecuzione delle Misure di Sicurezza (REMS) – were evaluated with the Trauma Experience Checklist (TEC) and the Millon Clinical Multiaxal Inventory (MCMI-III) to study lifetime traumatic memories and general psychopathology, respectively. Results. Preliminary findings show that about 41% (N=22) of psychiatric offenders were affected by PTSD, often not due to a single episode but to multiple lifetime traumas. Therefore, lifetime traumatic experiences and specifically sexual abuse are significant risk factors for the development of a personality disorder, which is present in the 38% (N=20) of the sample. Conclusions. The high PTSD prevalence and the strong association found between trauma and abuse with the development of a personality disorder emphasizes the importance of an early evaluation and intervention on traumatic experiences in this difficult population of psychiatric patients; in fact, the treatment of psychiatric offenders is actually vague and devoid of scientific evidence. Our results open up the perspective on the use of known and specific interventions for trauma, such as EMDR and Mindfulness.